Differences between Demographic Proportions, Socio-economic, and Health Status of the Elderly in West Java and Indonesia - Niken Firdaus; Ari Susanti; Sharon Gondodiputro (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
Purpose: This study aims to analyze differences between demographic proportion, socio-economic, and health status of the elderly in West Java and IndonesiaMethod: This study used a comparative analytic method with a retrospective approach. Furthermore, in this study, there was a unit of analysis, which was secondary data on demography, socio-economic, and health status of the elderly in 2014-2018 in West Java and Indonesia which was taken from the Indonesian Central Statistics Agency (Badan Pusat Statistik Indonesia).Result: The results of the study show that there is no difference in the demographic proportion in West Java and Indonesia in the age group, the status of living with the elderly, the marital status- married and divorced not remarried, and household membership status- head of household and other household membership status; However, there are differences in proportions the marital status-never married, widowed not remarried, the household membership status- wife/ husband and parents-in-law. Meanwhile, there is no difference in the socio-economic proportion in West Java and Indonesia in the status of residence ownership, residence eligibility, and household economic status. Furthermore, there is no difference in the health status proportion in West Java and Indonesia in the morbidity rate, duration of illness, outpatient care and inpatient care.Conclusion: there is no difference in the socio-economic proportion and health status of the elderly in West Java and in Indonesia. Meanwhile, there are differences in proportions demographics in West Java and Indonesia.